Transcendent God, Rational World A Maturidi Theology. - Harvey, Ramon (Edinburgh Studies in Islamic Scripture and Theology Ser., 2021)
Ramon Harvey revisits the Muslim theologian Abū Manṣūr al-Māturīdī (d. 333/944) from Samarqand and puts his system, and that of the Māturīdī school, into lively dialogue with modern thought to show that a contemporary Muslim philosophical theology (kalām jadīd) can provide original and constructive answers to perennial theological questions.